Editorial (An Idea Whose Time Has Come? An African Foresight Observatory on Genomics Medicine and Data-Intensive Global Science) - Dandara, Collet; Adebamowo, Clement; de Vries, Jantina; S. Dove, Edward; Fisher, Erik; A. Gibbs, Richard; J. Hotez, Peter; Kickbusch, Ilona; M. Knoppers, Bartha; Masellis, Mario; Z. Oestergaard, Mikkel; Pang, Tikki; et al. (Current Pharmacogenomics and Personalized Medicine, 2012)
Full Text Available.
Keywords: vaccinomics and personalized vaccines